Cultural differences in the workplace: a comparative study between French and Brazilian workers - Prevost, Louis Dimitri Charles (2020)
In the current context of globalization, workers from very different countries have come to work with each other. The study of intercultural workplace, and in particular the study of the characteristics of national cultures and their effect in the workplace, has therefore become an important topic. Understanding national culture is indeed very useful to improve the performance and the well-being of employees that must collaborate with foreign colleagues. It also improves the attractiveness and the effectiveness of the company that recognizes its importance. The current study aims at understanding cultural differences between French and Brazilian workers in French firms in Brazil. 172 workers, from French subsidiaries in Brazil, have participated in the research among which 93 are French and 79 are Brazilians. The study tends to show that French and Brazilian workers differ the most in terms of individualism/collectivism and long term/short term orientation but seem to be very similar when it comes to power distance, and Indulgence/Restraint. Implications are discussed for further training of French managers in Brazil and better understanding of French people by Brazilian workers.